Revealing the unseen: A brief review of invasive and non-invasive process tomography in industry - Ain Eazriena, Che Man; Yasmin, Abdul Wahab; Nurhafizah, Abu Talip @ Yusof; Suzanna, Ridzuan Aw; Mohd Mawardi, Saari; Ruzairi, Abdul Rahim; Yu, Sia Yee (Penerbit Universiti Teknologi Malaysia, 2025)
In the field of multiphase flow characterisation, process tomography techniques have attracted a lot of attention because they provide important insights into the internal dynamics of complicated systems. In particular, non-invasive and invasive techniques are compared and several forms of process tomography utilized for multiphase regime identification are reviewed in this work, with an emphasis on industrial applications. Non-invasive process tomography methods evaluate electrical qualities or fluctuations in conductivity using external sensors or electrodes, allowing for real-time imaging and monitoring without physically altering the system. In contrast, more precise and localized measurements are made possible by invasive process tomography techniques, which entail the direct insertion of sensors or probes into the system. The comparative benefits and drawbacks of invasive and non-invasive process tomography methods for multiphase regime identification are also included in this review. It examines variables like measurement precision, spatial resolution, intrusiveness of the system, and installation needs. When choosing process tomography methods for finding multiphase regimes in industrial applications, researchers can make well-informed selections with the help of this review, which provides insights into the advantages and disadvantages of each methodology.